2022
DOI: 10.3390/ma15145030
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of Empirical Relationships to Predict Cambodian Masonry Strength

Abstract: Masonry material characteristics, such as compressive strength, and the relationship between brick, mortar, and masonry compressive strengths are required for the analysis and assessment of masonry structures. This paper aimed to investigate the compressive strength relationship of Cambodian masonry. A total number of 42 prisms were constructed in the laboratory using six different brick/mortar combinations. Two brick types, solid and hollow, and three—1:3, 1:4, and 1:6—cement–sand mortar combinations were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…) Among these equations, which exclusively consider the compressive strengths of brick units and mortar, it was observed that the D. Leo [26], Euro Code-6 [25], Kumavat [27], and Engesser [28] equations tended to overestimate the compressive strength, with mean values of f m(pre )/f m(exp) all greater than 1.00 for both Group 1 and Group 2. Conversely, the Kandymove [47] equation underestimated fm. Alternatively, the Brocker [45] equation demonstrated varying results between Groups 1 and 2, with the mean value closely approximating unity (1.09) for Group 1 masonry specimens, while Group 2 masonry specimens were overestimated by approximately 1.5 times.…”
Section: Validation Of the Proposed Equationsmentioning
confidence: 81%
“…) Among these equations, which exclusively consider the compressive strengths of brick units and mortar, it was observed that the D. Leo [26], Euro Code-6 [25], Kumavat [27], and Engesser [28] equations tended to overestimate the compressive strength, with mean values of f m(pre )/f m(exp) all greater than 1.00 for both Group 1 and Group 2. Conversely, the Kandymove [47] equation underestimated fm. Alternatively, the Brocker [45] equation demonstrated varying results between Groups 1 and 2, with the mean value closely approximating unity (1.09) for Group 1 masonry specimens, while Group 2 masonry specimens were overestimated by approximately 1.5 times.…”
Section: Validation Of the Proposed Equationsmentioning
confidence: 81%